Mengembangkan Resource Advantage Theory Berbasis Nilai-Nilai Islam - Anindya Putri Utami; Nurul Rizka Arumsari; Budhi Cahyono (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research aims to integrate Resource Advantage (RA) Theory with Islamic values, especially the concept of maslahah, as a strategic approach to create a sustainable and ethical competitive advantage. RA Theory emphasizes the importance of superior resource management as a key factor in achieving a competitive position in the market. However, this theory tends to be oriented towards achieving financial benefits alone without paying attention to social or ethical aspects. On the other hand, the concept of maslahah in Islam prioritizes broader welfare, including benefits for individuals, society, and the environment, as well as avoiding harm. The integration of RA Theory with the maslahah principle offers a new conceptual framework that balances business interests with social responsibility. This approach emphasizes that resource management is not only geared towards maximizing profits, but also to provide sustainable and equitable benefits for all stakeholders. Thus, companies that implement strategies based on RA Theory and maslahah are expected to be able to effectively improve marketing performance while strengthening their reputation as business entities that are committed to ethical and sharia values. Furthermore, the implementation of this integration can help companies in dealing with the dynamics of the global business environment, including sustainability issues, corporate social responsibility, and consumer demands that are increasingly critical to business practices. The results of this research are expected to make a theoretical contribution by expanding the study of marketing management that is oriented towards ethics and sustainability, as well as practical contributions in the form of strategic recommendations for sharia-based and conventional companies that want to increase competitiveness through resource management based on Islamic values. Thus, this research not only enriches the academic literature, but also becomes a practical guideline for business actors in building sustainable, competitive, and equitable businesses.